THE COMPONENTS OF PEDAGOGICAL COMMUNICATION ARE ITS TASKS - Usmanova Kh. (Galaxy International Interdisciplinary Research Journal, 2022)
Pedagogical communication as a social-psychological process is characterized by the following functions: knowing the person; information exchange; organization of activities; exchange roles; concern for others; self-affirmation.